Evaluation of Cardiac Remodeling After Surgical Closure of Atrial Septal Defect in Different Age Groups (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: Cardiac remodeling manifested clinically as changes in size, shape and function of the heart. The extent of remodeling depends on initial morphological changes. So the time at which the surgical correction of atrial septal defect (ASD) done is important. Apparently surgical outcome and remodeling is better at earlier age in comparison to adult age. The aim of this study was to find whether surgical correction of ASD is beneficial at younger age (up to 18 years) in comparison to adult age (above 18 years).Methods: This prospective cohort study was carried out on a total of 70 patients who underwent surgical closure of atrial septal defect over a period of twenty three months (23) months (from February 2013 to December 2014) in the Department of Cardiac Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka. The recruited patients were divided into two groups – Group-A (comprised of ≤ 18 years old patients) and Group-B (comprised of >18 years old patients) 35 patients in each. Condition of the heart was evaluated preoperatively by echocardiography and the result was compared with postoperative echocardiographic findings at follow-ups after 1 and 3 months after surgery.Results: The comparison of echocardiographic parameters between baseline (preoperative) and those at 1 and 3 months after surgery in Group-A demonstrated that statistically significant remodeling occurred after 1st month (p < 0.001) and it further improved at 3 months. In Group-B the comparison of echo parameters between baseline and at 1 month revealed that all the parameters responded significantly indicating that remodeling occurred well after 1 month. But the same parameters when compared between baseline and at months after repair revealed insignificant differences in all the parameters, except PWT indicating that remodeling that occurred at month 1 regressed at 3 months interval. Cardiac remodeling occurred in both groups, but the degree of remodeling between patients of early age (Group-A) and late age (Group-B) revealed that ASD repair at early age responded well with respect to all the echocardiographic variables of remodeling.Conclusion: Cardiac remodeling occurs after surgical closure of atrial septal defect. But the degree of remodeling is better if the closure is done at earlier age (at or below 18 years).Ibrahim Card Med J 2018; 8 (1&2): 48-52